Oxycodone, an opioid like the others? - Marie, Nicolas; Noble, Florence (Frontiers in Psychiatry, 2023)
The over-prescription of opioid analgesics is a growing problem in the field of addiction, which has reached epidemic-like proportions in North America. Over the past decade, oxycodone has gained attention as the leading opioid responsible for the North America opioid crisis. Oxycodone is the most incriminated drug in the early years of the epidemic of opioid use disorder in USA (roughly 1999-2016). The number of preclinical articles on oxycodone is rapidly increasing. Several publications have already compared oxycodone with other opioids, focusing mainly on their analgesic properties. The aim of this review is to focus on the genomic and epigenetic regulatory features of oxycodone compared with other opioid agonists. Our aim is to initiate a discussion of perceptible differences in the pharmacological response observed with these various opioids, particularly after repeated administration in preclinical models commonly used to study drug dependence potential.